Patterned deposition of nanoparticles using dip pen nanolithography for synthesis of carbon nanotubes - Dahlberg, Kevin; Woods, Kelly; Jenkins, Carol; Broadbridge, Christine; Schwendemann, Todd C (Materials Research Society, 2015)
Ordered carbon nanotube (CNT) growth by deposition of nanoparticle catalysts using dip pen nanolithography (DPN) is presented. DPN is a direct write, tip based lithography technique capable of multi-component deposition of a wide range of materials with nanometer precision. A Nanolnk NLP 2000 is used to pattern different catalytic nanoparticle solutions on various substrates. To generate a uniform pattern of nanoparticle clusters, various conditions need to be considered. These parameters include: the humidity in the vessel, temperature, and tip-surface dwell time. By patterning different nanoparticle solutions next to each other, identical growth conditions can be compared for different catalysts in a streamlined analysis process. Fe, Ni, and Co nanoparticle solutions patterned on silicon, mica, and graphite substrates serve as nucleation sites for CNT growth. The CNTs were synthesized by a chemical vapor deposition (CVD) reaction. Each nanoparticle patterned substrate is placed in a tube furnace held at 725°C during CNT growth. The carbon source used in the growth chamber is toluene. The toluene is injected at a rate of 5 mL/hr. Growth is observed for Fe and Ni nanoparticle patterns, but is lacking for the Co patterns. The results of these reactions provide important information regarding efficient and highly reproducible mechanisms for CNT growth. © 2015 Materials Research Society.
Keywords: Carbon nanotubes; Catalysts; Catalytic nanoparticle; Chemical vapor deposition; Chemical vapor depositions (CVD); Deposition; Dip-pen nanolithography; Lithography; Mica; Nanolithography; Nanoparticle catalysts; Nanoparticle clusters; Nanoparticle solutions; Nanoparticles; Nanotubes; Nickel; Patterned deposition; Patterned substrates; Silicate minerals; Substrates; Synthesis (chemical); Toluene; Vapor deposition; Yarn; dept.phy

Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success - Ferrari, Nicole; Jenkins, Carol; Garofano, Jacquelynn; Day, Deborah A; Schwendemann, Todd C; Broadbridge, Christine (Materials Research Society, 2015)
Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experiences, the value of interdisciplinary skill development is integral to the REU experience and these contributions may warrant a more formal evaluative definition. Using the emerging 21st Century Skills Framework, CRISP has begun conducting a series of small-scale studies in an effort to define the contribution of student research experiences in cross-disciplinary skill development and the positive effects that exposure to real-world science practices have on refinement of career decisions and vocational success. Using Likert-type survey methods, this study directly examines current and former REU students' perceptions of the importance of interdisciplinary 21st century skills such as creativity, collaboration, communication, information literacy, and problem-solving in their REU experience and their perceived value of these skills in their future and/or current careers. Through better understanding the role these "soft skills" play in student research experiences, CRISP hopes to maximize these interdisciplinary benefits within its REU program to best prepare students for the complex demands of the 21st century workplace. © 2015 Materials Research Society.
Keywords: Amphibious vehicles; Cross-disciplinary; Education; Engineering research; Functions; Information literacy; Interdisciplinary skills; Interface structures; Problem solving; Research Experiences for Undergraduates programs; Research experiences for students; Research-based experiences; Skill development; Students; dept.phy